2011
DOI: 10.2320/matertrans.m2010363
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and Corrosion Characteristics of Iron-Silicon Alloyed Layer on 5083 Al Alloy by Electrical Discharge Alloying Processing

Abstract: In the study, the surface modification of 5083 Al alloy by electrical discharge alloying (EDA) with a 75 mass% ferrosilicon electrode was used to examine the effects of machining parameters (discharge current, pulse duration and duty factor) on the thickness, hardness and surface roughness of the alloyed layer. Experiment results reveal that the thickness tends to increase with the increase in the pulse duration and discharge current. In addition, the micro-hardness evidently higher compared to the substrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This may be related to the formation of carbides that contain Cr in the layer. Lin et al 71 performed EDA on 5083 Al alloy with a 75% by mass of ferrosilicon electrode. It was reported that the thickness of iron–silicon layer increases with an increase in pulse duration and discharge current (Figure 39).…”
Section: Electro-discharge Alloyingmentioning
confidence: 99%
“…This may be related to the formation of carbides that contain Cr in the layer. Lin et al 71 performed EDA on 5083 Al alloy with a 75% by mass of ferrosilicon electrode. It was reported that the thickness of iron–silicon layer increases with an increase in pulse duration and discharge current (Figure 39).…”
Section: Electro-discharge Alloyingmentioning
confidence: 99%
“…The main factors that affect the thickness of alloyed layers are the nature of tool electrodes and the parameters of the EDA process. 16,17,20,23,25,34) Some researchers point out that the melting point, thermal and electric conductivity of the electrodes all affect the thickness. 23,25,34) Wang et al 23) examined the mechanism with which the EDM process was employed to form strengthening layers in the surface of stainless steel and the main factors that affected this mechanism.…”
Section: Microstructural Observation Of Edaed Layersmentioning
confidence: 99%
“…The transmission electron microscopy (TEM) study revealed the matrix formation of fine needles of Si particles, blocks of nano-size Al 4 Fe 5 Si and Al 3 Fe 4 particles. In addition, this layer exhibited good corrosion resistance in NaCl aqueous solution [8,9]. Nihal et al [10] used hydroxyapatite powder mixed dielectric liquid and proved that the collision of the powder separates the main discharge which made the surface rich in additives.…”
Section: Introductionmentioning
confidence: 99%